Patients’, parents’, and survivors’ perspective about AI applications in pediatric oncology - Hyseni Bocolli Albina; Schneider Carina; Bastos Pais Teresa; Willi Michaela; Brunmair Mattias (EJC Paediatric Oncology)
Patients, parents and survivors of childhood cancer are those who represent the critical link between the clinical and technical research spheres. Thus, UNICA4EU worked towards a patient- centric approach to integrate AI in the care pathways for childhood cancer, with evidence-based patient advocacy at its core to build trust while protecting and guaranteeing patients’ fundamental rights [1].The task “Increase Knowledge and Transparency about AI among patients, parents and survivors” was led by CCI Europe as the biggest pan-European childhood cancer parents’ and survivors’ organization which represents childhood cancer parents´ and survivors´ groups and other childhood cancer organizations and reunites 63 member-organizations in 34 countries [2].To investigate the knowledge base of AI application in pediatric oncology among those who are affected, a survey was conducted. The survey translated into nine European languages, gathered responses from 332 individuals. To delve deeper into the survey findings, discussions were held with a diverse focus group, including four parents of childhood cancer former patients (survivors), three childhood cancer survivors, and one bereaved parent, each representing different backgrounds, age groups, and countries.Insights and outcomes of this study produced a report for guiding the multi-stakeholder board of the project when defining the governance structures reg. data sharing, ownership, protection, access and usage.Perspective of parents, patients and survivors of pediatric cancer regarding AI applications in Pediatric Oncology focused in six areas of interest including: data anonymization and data protection, data ownership, data withdrawal, ethical concerns of use of data, data types and, additionally, informed consents. This paper summarizes the respective results, along concluding policy recommendations.